2019
DOI: 10.2106/jbjs.oa.18.00028
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Weakness in Individuals with Coexisting Medial and Lateral Osteoarthritis

Abstract: Background: This study examined whether individuals who have mild medial osteoarthritis (OA) of the knee with coexisting lateral OA have less muscle strength than individuals who do not have lateral OA. Methods: A series of 153 individuals (84% of whom were women) between 48 and 88 years old who had Kellgren and Lawrence (KL) grade-2 OA in the medial compartment of the knee underwent radiographic evaluation to assess the presence of lateral OA, which was graded with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Hicks et al indicated that knee pain accompanied by decreased knee extension strength and standing balance was significantly correlated with the risk of multiple falls in older people [ 5 ]. Patients with OA knee frequently presented progressive knee pain and quadriceps weakness [ 6 ], and these problems can even be exacerbated during the early stage following TKR [ 7 ]. These factors will increase the risk of falling during early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Hicks et al indicated that knee pain accompanied by decreased knee extension strength and standing balance was significantly correlated with the risk of multiple falls in older people [ 5 ]. Patients with OA knee frequently presented progressive knee pain and quadriceps weakness [ 6 ], and these problems can even be exacerbated during the early stage following TKR [ 7 ]. These factors will increase the risk of falling during early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Proprioceptive sensitivity attributable to fibrous capsules in skeletal muscles, tendons, and joints decreases in knee OA due to the degenerative changes of these structures (Jeong et al, 2019). It has also been emphasized that quadriceps muscle weakness, one of the most important findings of knee OA, may result from disuse atrophy due to pain, which is one of the symptoms of OA (Iijima et al, 2019). Furthermore, quadriceps strength loss may be a risk factor in the further development and progression of knee OA, based on the fact that quadriceps muscle strength affects OA symptoms, such as pain and loss of function (Onwunzo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%